What Really Causes Necrotising Enterocolitis?. (17th December 2012) - Fox, Thomas Peter; Godavitarne, Charles
Abstract : Background . One of the most serious gastrointestinal disorders occurring in neonates is necrotising enterocolitis (NEC). It is recognised as the most common intra-abdominal emergency and is the leading cause of short bowel syndrome. With extremely high mortality and morbidity, this enigmatic disease remains a challenge for neonatologists around the world as its definite aetiology has yet to be determined. As current medical knowledge stands, there is no single well-defined cause of NEC. Instead, there are nearly 20 risk factors that are proposed to increase the likelihood of developing NEC. Aims and Objectives . The aim of this project was to conduct a comprehensive literature review around the 20 or so well-documented and less well-documented risk factors for necrotising enterocolitis. Materials and Methods . Searches of the Medline, Embase, and Science direct databases were conducted using the words "necrotising enterocolitis + the risk factor in question" for example, "necrotising enterocolitis + dehydration." Search results were ordered by relevance with bias given to more recent publications. Conclusion . This literature review has demonstrated the complexity of necrotising enterocolitis and emphasised the likely multifactorial aetiology. Further research is needed to investigate the extent to which each risk factor is implicated in necrotising enterocolitis.